The Representation of Women in Muhammad Husain Haikal's Novel Zainab: A Semiotic Study - Muhammad Zidane Alfarizi; Dedi Supriadi (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to dismantle the representation of women in Muhammad Husain Haikal’s novel Zainab through a semiotic approach. As the first modern novel in Arabic literature, Zainab does not merely present a romantic narrative but serves as a critical portrait of the Egyptian social structure in the early 20th century. This research employs a descriptive-analytical method, utilizing Roland Barthes’ semiotic framework which focuses on three levels of signification are denotation, connotation, and myth (ideology). Data were collected through close-reading and note-taking techniques, followed by an in-depth analysis to establish the connection between linguistic signs and socio-cultural realities. The findings reveal that the figure of Zainab is represented through five primary constructions 1) Economic exploitation through an asymmetric wage system, 2) The myth of institutionalized suffering through the symbol of the weary body, 3) Critique of domestic authority regarding forced marriage, 4) The commodification of women within the feudal marriage market, and 5) The synthesis of female suffering with the homeland through an ecofeminist perspective. These results uncover that Haikal employs the female figure as a medium to challenge patriarchal ideology and the feudal system (Izbah) that constrains female agency. Consequently, this study reaffirms the position of the novel Zainab as a social manifesto demanding humanitarian transformation and gender justice amidst the tensions between tradition and modernity